PENGGUNAAN METODE JIGSAW DALAM PEMBELAJARAN MATA KULIAH TRANSLATION UNTUK MENGHASILKAN KEEFEKTIFAN DALAM MENYELESAIKAN TERJEMAHAN - Zanah, Sri Wahyuni Samaratul; Annaningtyas, Cucut (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
Translation learning is a complex process that requires a profound understanding of both the source and target languages. This study aims to explore the use of the Jigsaw method in the context of translation course learning, with a focus on enhancing students' effectiveness in completing translations. The Jigsaw method is a cooperative learning approach where students work in small groups to understand parts of the material and then take responsibility for teaching that material to other group members. This study integrates the Jigsaw method into translation learning by utilizing complex and varied source language texts. Students are divided into small groups and assigned tasks to study specific sections of the text to be translated. After thoroughly understanding their respective sections, they regroup with other members who have studied different parts. Through collaboration and discussion, students exchange information and discuss translation strategies. The results of this study indicate that the use of the Jigsaw method significantly enhances students' effectiveness in completing translations. Collaboration among students allows for the exchange of ideas and strategies that can improve their understanding of the source text and produce more accurate and detailed translations. Additionally, through this cooperative learning process, students also develop important social and communication skills essential in the translation profession.